Somalia Economic Update, June 2021 : Investing in Health to Anchor Growth - World Bank (World Bank, Washington, DC, 2021)
Somalia Economic Update reports aim to contribute to policymaking and the national conversations on topic issues related to economic recovery and development. The report contains three main messages. The COVID-19 pandemic exposed the costs of not investing in a public health system. The near-term economic prospects for Somalia depend on the pandemic’s path. Public spending on health is crucial to support testing and tracing and ensuring that the logistical, administrative, and financial requirements of mass vaccination are in place. The slower the pace of vaccination and the larger the unvaccinated population, the greater the possibility that new variants of the virus will develop, increasing the prospect of a more protracted pandemic.